2001
DOI: 10.1128/mcb.21.3.731-742.2001
|View full text |Cite
|
Sign up to set email alerts
|

Transcript Lifetime Is Balanced between Stabilizing Stem-Loop Structures and Degradation-Promoting Polyadenylation in Plant Mitochondria

Abstract: To determine the influence of posttranscriptional modifications on 3 end processing and RNA stability in plant mitochondria, pea atp9 and Oenothera atp1 transcripts were investigated for the presence and function of 3 nonencoded nucleotides. A 3 rapid amplification of cDNA ends approach initiated at oligo(dT)-adapter primers finds the expected poly(A) tails predominantly attached within the second stem or downstream of the double stem-loop structures at sites of previously mapped 3 ends. Functional studies in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
57
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 29 publications
3
57
0
Order By: Relevance
“…However, using oligo(dT)-based RT-PCR approaches, we and others (22)(23)(24)(25) have shown that mRNAs may be polyadenylated at low levels. The use of the cRT-PCR technique allows in theory the analysis of both the 3Ј-and 5Ј-ends of transcripts regardless of the polyadenylation status of the transcripts.…”
Section: Resultsmentioning
confidence: 99%
“…However, using oligo(dT)-based RT-PCR approaches, we and others (22)(23)(24)(25) have shown that mRNAs may be polyadenylated at low levels. The use of the cRT-PCR technique allows in theory the analysis of both the 3Ј-and 5Ј-ends of transcripts regardless of the polyadenylation status of the transcripts.…”
Section: Resultsmentioning
confidence: 99%
“…The pea mitochondrial atp9 gene was chosen as standard substrate because this gene is abundantly transcribed and has been investigated in detail with respect to its promoters and transcript stability (22,23). It is furthermore efficiently edited at most of its editing sites, 2 including the first site in the reading frame, which was selected as the editing target.…”
Section: The In Vitro Editingmentioning
confidence: 99%
“…Polyadenylation is required for stabilizing virtually all nuclear-encoded mRNAs in all eukaryotes. In contrast, polyadenylation targets mRNAs for degradation in eubacteria (1,2), chloroplasts (3)(4)(5)(6), plant mitochondria (7)(8)(9), and trypanosome mitochondria (10). In eubacteria and chloroplasts, degradation of mRNAs is initiated by endonucleolytic cleavages.…”
mentioning
confidence: 99%
“…Maize cox2 mRNAs may also be polyadenylated, although the influence of polyadenylation on the degradation rate in vitro is less pronounced (8). Recently, polyadenylation of pea atp9 and Oenothera atp1 transcripts has also been characterized (9). Both transcripts terminate with a stable double stem-loop structure, which compensates to some extent for the destabilization effect of polyadenylation in vitro (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation